Optimization of Wet Noodle Formulation Fortified with Spirulina platensis L. Powder Using D-Optimal Mixture Design: Optimasi Formula Produk Mi Basah Terfortifikasi Bubuk Spirulina platensis L. Menggunakan D-Optimal Mixture Design - Setyawan, Hendrix Yulis; Eka Wahyu Belianna; Afifal, Lana Izzatul; Damayanti, Devi Dwi; Shafira, Dhea Aura Bening; Wijayanti, Karlina (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2025)
Abstract The productive life of Indonesian people encourages the consumption of cheap and practical instant noodles, with 3.8% consuming them more than once a day. However, the low protein content of instant noodles requires fortification, one of which is with Spirulina platensis powder which contains high protein up to 71.90%. This study aims to determine the optimum proximate conditions of wet noodles fortified with spirulina powder using Design Expert 13 software with the D-optimal mixture design method. The variables tested were spirulina powder with an upper limit of 3.75 grams and a lower limit of 0 grams, and tapioca flour with an upper limit of 7.5 grams and a lower limit of 3.75 grams. The results of statistical tests showed that spirulina powder was significant on protein and carbohydrate levels (F<0.05), but not significant on water, ash, and fat levels (F>0.05). The best formulation was obtained at 3.75 grams of tapioca and 3.75 grams of spirulina with a water content of 32.06%, ash 2.49%, protein 18.96%, fat 1.78%, carbohydrate 44.71% which met the wet noodle standards in SNI 01-2987-2015. Abstrak Kehidupan produktif masyarakat Indonesia mendorong konsumsi mi instan yang murah dan praktis, dengan 3,8% mengonsumsinya lebih dari sekali per hari. Namun, kandungan protein mi instan yang rendah memerlukan fortifikasi, salah satunya dengan bubuk Spirulina platensis yang mengandung protein tinggi hingga 71,90%. Penelitian ini bertujuan untuk menentukan kondisi optimum proksimat mi basah terfortifikasi bubuk spirulina menggunakan software Design Expert 13 dengan metode D-optimal mixture design. Variabel yang diuji adalah bubuk spirulina dengan batas atas 3,75 gram dan batas bawah 0 gram, serta tepung tapioka dengan batas atas 7,5 gram dan batas bawah 3,75 gram. Hasil uji statistik menunjukkan bubuk spirulina signifikan terhadap kadar protein dan karbohidrat (F<0,05), tetapi tidak signifikan terhadap kadar air, abu, dan lemak (F>0,05). Formulasi terbaik diperoleh pada 3,75 gram tapioka dan 3,75 gram spirulina dengan kadar air 32,06%, abu 2,49%, protein 18,96%, lemak 1,78%, dan karbohidrat 44,71% yang telah sesuai standar mi basah pada SNI 01-2987-2015.